The Human Rights and Social Justice Scholars Program: A Collaborative Model for Preclinical Training in Social Medicine - Salina Bakshi; Aisha James; Marie Oliva Hennelly; Reena Karani; Ann-Gel Palermo; Andrea Jakubowski; Chloe Ciccariello; Holly Atkinson (Ubiquity Press, 2015)
Background: Despite the importance of the role social justice takes in medical professionalism, the need to train health professionals to address social determinants of health, and medical trainees' desire to eliminate health disparities, undergraduate medical education offers few opportunities for comprehensive training in social justice. The Human Rights and Social Justice (HRSJ) Scholars Program at the Icahn School of Medicine at Mount Sinai is a preclinical training program in social medicine consisting of 5 components: a didactic course, faculty and student mentorship, research projects in social justice, longitudinal policy and advocacy service projects, and a career seminar series. Objectives: The aim of this article is to describe the design and implementation of the HRSJ curriculum with a focus on the cornerstone of the HRSJ Scholars Program: longitudinal policy and advocacy service projects implemented in collaboration with partner organizations in East Harlem. Furthermore, we describe the results of a qualitative survey of inaugural participants, now third-year medical students, to understand how their participation in this service-learning component affected their clinical experiences and professional self-perceptions. Conclusion: Ultimately, through the implementation and evaluation of the HRSJ Scholars Program, we demonstrate an innovative model for social justice education; the enduring effect of service-learning experiences on participants' knowledge, skills, and attitudes; and the potential to increase community capacity for improved health through a collaborative educational model.